HUBUNGAN POSISI KERJA PADA PEKERJA INDUSTRI BATU BATA¬ DENGAN KEJADIAN LOW BACK PAIN - Erwin ' Rinaldi; Wasisto ' Utomo; Fathra Annis Nauli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Safety at working area still largely ignored by workers. Low back pain was the most frequent musculoskeletal complaint. The purpose of this study was to identify the image position of working on brick industry workers, identified the risk incidence of low back pain, identified the risk incidence of low back pain, and also identify the relationship between the working position on brick industry workers with the risk of low back pain incidence. The method of study is descriptive correlation with cross sectional study. The study conducted on 52 respondents in the district Benai by using purposive sampling technique. The analysis used an univariat and bivariat with alternative test kolmogorov smirnov. The result showed that 33 workers (63,5%) are middle age, work >5 years as much 23 workers (44,2%), totally lift brick 5.100-8.499 kg as much 24 workers (46,2%) and workers are working >7 hour/days as much 29 workers (55,8%). The analysis bivariat showed significant correlation between the working position on brick industry workers with the risk incidence of low back pain (p value 0,002 <0,05). The result of this research can be input to the labor department to explain the return to health workers about the principles of safety, and the results of this study should be useful for other researchers as a basis or benchmark data relating about low back pain in terms of others. Recommended for the labor offices to get action with K3 for every workers to avoid work accident, by make a tool to facilitate the activities or workers and to disseminate the correct working position. Keywords :working position, low back pain, brick industry workers